WILD CLUSTER BOOTSTRAP CONFIDENCE INTERVALS - MacKinnon, James (L'Actualité économique)

(untitled) (HEC Montréal, 2020)
Confidence intervals based on cluster-robust covariance matrices can be constructed in many ways. In addition to conventional intervals obtained by inverting Wald (t) tests, the paper studies intervals obtained by inverting LM tests, studentized bootstrap intervals based on the wild cluster bootstrap, and restricted bootstrap intervals obtained by inverting bootstrap Wald and LM tests. It also studies the choice of an auxiliary distribution for the wild bootstrap, a modified covariance matrix based on transforming the residuals that was proposed some years ago, and new wild bootstrap procedures based on the same idea. Some procedures perform extraordinarily well even with the number of clusters is small.